Preparation of an Organic Phosphore Compound and Use in Extracting Fe(III) from Phosphoric Acid Solution by Liquid-Liquid Extraction Method (Latakia University Journal -Basic Sciences Series, 2021)
Ñ  ABSTRACT   ÑThe study addresses the preparation of organic phosphore compound that have the P-NH-P bridge, They have the following chemical formula (PhO)2P(O)-NH-P(O)(PhO)2 become the name μ- imido tetraphenyl aster diphosphoric acid. It takes the abbreviation TPhOO, it used as extractant for iron(III) in liquid – liquid extraction method, where was identified some of the physical properties for its, Lesson of Partition Coefficient Iron D brtween the aqueous medium of iron(III) in phosphoric acid 0.1N and organic medium toluene containing different concentrations of organic phosphorus compound prepared previously and distribution information was evaluated numerically and graphically and as a result, the previously compound reacts with the iron (III) ion in the ratio [1: 3].To verify obtain the required compound and its complex we study it by using IR and UV-Visible technology. Then we concluded that the prepared compound and its complex coincided with those that have been proposed.